The order to fill the post of head of state: the problems of the oretical and practice - Лукаш, Олена Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article realization comparative analyses of order to fill the post of head of state in monarchy and republic, exploration the systems of succession to the throne. It was concluded about strengthening tendencies decentralizationof electoral laws, which regulations the order to fill the post of head of state.